IN SITU MEASUREMENTS OF ATMOSPHERIC GAMMA RADIATION IN THE GAS FLARING ENVIRONMENT OF THE OLOGBO TOWN, NIGERIA. - B.U., Onosohwo,; E.W., Mangset,; M.U., Khandaker, (Malaysian Journal of Science, 2014)
The atmospheric gamma radiation level in gas flaring environment has gained the attention of researchers and environmentalists due to its devastating impact both on the climate and the environment. It is important to make a quantitative assessment of the gamma radiation in the gas flaring environment and nearby residential areas. In situ measurements of the gamma radiation were performed using a nuclear radiation monitoring device: Digilert-50, Stop watch and a geographical positioning system. Data were collected from two different locations: Ologbo town and 40m away to the flaring site. Measured data showed that the mean equivalent dose rate at 40m away to the flaring site during flaring period was 1.02mSv/yr, and at Ologbo town was 1.04mSv/yr. The obtained dose rate in the flaring site and Ologbo town area exceeded the International Atomic Energy Agency and International Commission on Radiological Protection recommended safety limit (>1mSv/yr.) for the general public. This shows that the flaring activities have impacted the surrounding environment radiologically. This may pose long-term health side effects on the workers and residents of the host communities. We recommend that flaring should not be done where human population is high or near residential areas because of the radon gas released. (Keyword: Gas flaring, Ologbo town, Atmospheric gamma radiation, In-situ measurements, General public)